2015
DOI: 10.1109/tsg.2014.2385636
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging AMI Data for Distribution System Model Calibration and Situational Awareness

Abstract: The many new distributed energy resources being installed at the distribution system level require increased visibility into system operations that will be enabled by distribution system state estimation (DSSE) and situational awareness applications. Reliable and accurate DSSE requires both robust methods for managing the big data provided by smart meters and quality distribution system models. This paper presents intelligent methods for detecting and dealing with missing or inaccurate smart meter data, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…To deal with the missing or inaccurate smart meter data, the paper [49] has used the pseudo measurement generator that utilizes a weighted average combination of historic data and interpolated/extrapolated data from previous or future measurements. Positive sequence equivalent models are used for parameter estimation.…”
Section: Smart Gridmentioning
confidence: 99%
“…To deal with the missing or inaccurate smart meter data, the paper [49] has used the pseudo measurement generator that utilizes a weighted average combination of historic data and interpolated/extrapolated data from previous or future measurements. Positive sequence equivalent models are used for parameter estimation.…”
Section: Smart Gridmentioning
confidence: 99%
“…Studies [7,8,[10][11][12][13][14][15]17,18,24,25,27,29] show the application of this approach to validate proposed strategies or devices. In summary, the following are examples of typical applications for snapshot analysis and validation:…”
Section: Time-sequential Simulationmentioning
confidence: 99%
“…For instance, studies [7,9,[14][15][16][19][20][21][22][23][24][26][27][28]30] show that the information obtained from this approach is compelling evidence for design and corroboration in many applications. In summary, the following are growing uses of time-sequential simulations in smart grid studies: It is possible to classify several time-sequential simulation approaches in terms of the ratio of computation time over simulated time.…”
Section: Time-sequential Simulationmentioning
confidence: 99%
“…A recent study [7] found the number of installed smart meters in the United States to have reached 45.8 million, which represents a penetration level of approximately 30%. Other researchers [8][9][10][11] established that AMI systems fail to record between 2.7% and 9.4% of meter readings in a given year.…”
Section: Introductionmentioning
confidence: 99%